Holistic Sustainability Assessment of Certified Organic, Non-Certified Organic, and Non-Organic Rice Farming Practices Using SAFA Framework in Sleman Regency, Indonesia - Romadhona, Sukron; Puryono, Sri; Mussadun; Rachmawati, Siti (AGRARIS: Journal of Agribusiness and Rural Development Research, 2024)
Sustainable development on a regional scale can be accelerated if organic farming management methods are adopted in Indonesia. This research utilized the Sustainability Assessment of Food and Agriculture (SAFA) framework due to its comprehensive coverage of sustainability and accessibility for producers and decision-makers. This study compared the sustainability of certified and non-certified organic as well as non-organic farms in Sleman Regency across four dimensions: good governance, environmental integrity, economic resilience, and social welfare, focusing on how different farming practices impact sustainability indicators. A total of 9 farmer groups participated in this study, categorized based on their farming practices and certification. The results unveiled that certified organic rice farming achieved the highest sustainability score. Specifically, certified organic farmer groups excelled in the economic sub-themes of product quality and information (82%) and local economy (90%), as well as the social sub-themes of labor rights (86%) and equality (80%). Meanwhile, non-certified organic farming performed highly in the local economy sub-theme (82%). In contrast, non-organic farming scored the highest in the sub-themes of investment economy (80%) and fair-trade practices (81%) but demonstrated low scores in holistic management (40%) and impact on the atmosphere (36%). Hence, certified organic rice farming outperformed non-certified organic and non-organic practices regarding sustainability. Key factors affecting farm sustainability included organic fertilizers, sustainable water management, local economic improvement, equity, labor conditions, biodiversity preservation, and product quality and information. These findings highlight the significance of adopting certified organic farming to achieve higher sustainability in agriculture.